Optimalisasi Pembelajaran Sistem Informasi Akuntansi dengan Penyusunan Aplikasi berbasis Excel dalam Mendukung Strategi Pemasaran dan Keuangan Digital - Oktaviani, Siska Aprilia; Oryza Ardhiarisca; Fitriya Andriyani; Berlina Yudha Pratiwi; Candra Pramula Pinandita (Politeknik Negeri Jakarta, 2024)
This study aims to examine the effectiveness and satisfaction of students with accounting information systems education through the development of Excel-based applications in enhancing their understanding of accounting information systems and digital financial strategies, as well as to evaluate its impact on strengthening digital marketing strategies. The research simultaneously explores the use of simple technology-based accounting education, such as Excel, with two important dimensions in digital business: finance and marketing. The results of the regression analysis indicate that understanding accounting information systems and the integration of digital financial strategies have a significant influence on the satisfaction and effectiveness of learning, while the strengthening of digital marketing strategies does not show a significant impact. These findings suggest that while the development of Excel-based applications is effective in supporting digital financial aspects, a different or additional approach is needed to strengthen digital marketing capabilities. This study arises from the urgent need to develop learning methods that not only enhance theoretical understanding but also practical skills relevant to the workforce in the digital era. Therefore, it is hoped that this research can contribute to the development of a more holistic and integrated curriculum that can more effectively prepare students to face challenges in the digital industry.